Pengaruh Modal, Tenaga Kerja dan Jam Kerja terhadap Pendapatan Pedagang Ikan di Desa Ranggi Kecamatan Wae Ri’i - Leonardus W Dino Setiawan; Bonefasius Berdi (Journal of Management and Creative Business, 2025)
This study aims to determine the effect of Capital, Labor and Working Hours on the Income of Fish Traders in Ranggi Village, Wae Ri’i District, data collection using primary data obtained from distributing questionnaires to fish traders in Ranggi Village, Wae Ri’i District. The population in this study were all fish traders totaling 30 people while the sample taken was 30 respondents. The testing method used SPSS 26 management. The results of the questionnaire have been tested for validity, reliability, classical assumptions in the form of normality tests, multicollinearity, heteroscedasticity, multiple linear analysis, determination coefficients and hypothesis testing. The results of the study showed that the proposed hypothesis was accepted because it showed significant partial hypothesis test results. This means that capital has a significant effect on the income of fish traders, this is known from the sig. value of the capital variable (X1) on the income of traders (Y) of 0.336 <0.05 and the T count value of 2.209> T table value of 2.042. The labor force has a significant effect on traders’ income, as can be seen from the sig value of the labor variable (X2) on traders’ income (Y) of 0.048 < 0.05 and the calculated T value is 2.078 > calculated T value 2.078 > table T value 2.042. Working hours have a significant effect on fish traders’ income from the sig. value of the working hours variable (X3) on income (Y) of 0.000 <0.05 and the calculated T value of 4.960> T table value of 2.042. The simultaneous influence between capital (X1), labor (X2) and working hours (X3) has a significant effect on fish traders’ income (Y) F count 17.801> F table value 3.32.